Detection of methyl isocyanate (CH3NCO) in a solar-type protostar. Issue 2 (17th April 2017) - Martín-Doménech, R.; Rivilla, V. M.; Jiménez-Serra, I.; Quénard, D.; Testi, L.; Martín-Pintado, J.
Abstract: We report the detection of the pre-biotic molecule CH3 NCO in a solar-type protostar, IRAS16293−2422 B. A significant abundance of this species on the surface of the comet 67P/Churyumov–Gerasimenko has been proposed, and it has recently been detected in hot cores around high-mass protostars. We observed IRAS16293−2422 B with the Atacama Large Millimeter Array in the 90 to 265 GHz range, and detected eight unblended transitions of CH3 NCO. From our Local Thermodynamic Equilibrium analysis, we derived an excitation temperature of 110 ± 19 K and a column density of (4.0 ± 0.3) × 10 15 cm −2, which results in an abundance of ≤(1.4 ± 0.1) × 10 −10 with respect to molecular hydrogen. This implies a CH3 NCO/HNCO and CH3 NCO/NH2 CHO column density ratios of ∼0.08. Our modelling of the chemistry of CH3 NCO suggests that both ice surface and gas phase formation reactions of this molecule are needed to explain the observations.